UI/UX Design of E-Learning Applications AL MUNADI SMA Case Study With A User Centered Design Approach - Joko Bintarto (University of Science and Computer Technology, 2023)
Technology the more develop every the day , Source Power Humans (HR) are required For follow development technology . Sector education is a must too follow development technology , Because education is Foundation main in management knowledge And knowledge .Manual learning and _ _ structured become reject measuring change in world education . So from That need a breakthrough new in field technology education namely with e- Learning design that can be done encourage teachers and student can Study And understand technology with walk side by side . For an e- Learning is required User Interface (UI) And User Experience (UX) so that a e- Learning display becomes more interesting And become Power pull alone i.